Peter Bramwell. ’Pagan Themes in Modern Children’s Fiction: The Green Man, Shamanism, Earth Mysteries’ - Comer, Dawn (Pomegranate, 2010)
Peter Bramwell, Pagan Themes in Modern Children’s Fiction: The Green Man, Shamanism, Earth Mysteries (New York: Palgrave Macmillan, 2009), 240 pp., 80 (cloth).